INVESTIGATING THE ASSOCIATION BETWEEN NURSE STAFFING LEVELS AND PATIENT OUTCOMES - Mathayil Lafi Majed Alanazi, Obaid Saad Aldawssary, Abdullah Awadh Sadan Rashdi, Mubarak Abdullah Saeed Al Dosery, Anoud Owead Hantan Alanzi, Saud Hassan Munawir Alharbi, Najwa Mohammed Zain, Maryam Mansour Kabi, ,; Alanood Mateb Al Harbi, Sami Faisal Alotibi, Akkash Labdan Alotaibi, Abeer Sweilem Yahya Alharthy, Khald Mubark Al Osaimi, (Chelonian Research Foundation, 2022)
Studies have shown connections between the number of nurses working and negative outcomes for patients, such as death while in the hospital. Nevertheless, the cause-and-effect aspect of this link is questionable. It has been suggested that omissions of nursing care, also known as missed care, care left undone, or rationed care, might serve as a more direct indication of the adequacy of nurse staffing. The objective of this study is to identify the nursing care that is most often overlooked in acute adult inpatient wards and to establish the evidence linking missed care to nurse staffing levels. We conducted a comprehensive search in the Cochrane Library, CINAHL, Embase, and Medline databases to identify quantitative studies that examine the relationships between staffing levels and instances of missed care. We conducted a comprehensive search of prominent academic publications, personal libraries, and reference lists of relevant papers. More than 75% of nurses reported intentionally not providing some aspects of care. Fourteen researches have shown a substantial correlation between low nurse staffing levels and increased claims of missing care. There was insufficient data to suggest that the addition of support workers to the team had a significant impact on reducing missed care. In hospitals, there is a correlation between insufficient staffing of Registered Nurses and instances of reported neglected nursing care. Missed care serves as a reliable measure of the sufficiency of nurse staffing. The degree to which the observed associations really indicate failures has not yet been studied. Keywords: association, nurse staffing levels, patient outcomes, review.